Cultivo de hongos comestibles utilizando desechos agricolas e industriales - Grodzinskaya, A.A.=700 1 Infante J., D.; Piven, N.M.
(Es, En)
ilus., 11 ref.
Keywords: CULTIVO; AGARICALES; SETAS COMESTIBLES; FRUCTIFICACION; MICELIO; LENTINUS EDODES; PLEUROTUS OSTREATUS; SUBSTRATOS; DESECHOS AGRICOLAS; DESECHOS INDUSTRIALES; VENEZUELA; STROPHARIA RUGOSOANNULATA